STUDI ANALISIS SYARAH HADIS LARANGAN MENUTUP MULUT KETIKA SALAT: SINKRONISASI LARANGAN DALAM HADIS DENGAN ANJURAN MENGENAKAN MASKER DI MASA PANDEMI COVID-19 - Salman Zulfahmi (Al-Majaalis : Jurnal Dirasat Islamiyah, 2021)
The presentation in this study discusses the description of the hadith regarding the prohibition of covering one's mouth during the Covid-19 pandemic. In achieving the results and discussion of this study using a qualitative approach through literature study by applying the takhrij hadith and syarah hadith methods. Determination of the quality of the hadith refers to the assessment of Al-Hakim and Al-Albani. The interpretation is used to analyze contemporary issues related to the Covid-19 outbreak by applying several kaidah fiqh and usul fiqh. This study concludes that the hadith that prohibits covering one's mouth when praying is issued and judged as hasan and shahih by several muhaddis. Wearing a mask when praying during the Covid-19 pandemic does not include violating the prohibitions contained in the hadith and if the danger of Covid-19 disappears or does not exist, the application of the prohibitions contained in the hadith will return to its original state. This research opens research opportunities to discuss all things that are prohibited or recommended in the hadiths but at first glance cannot be applied to certain conditions.